Surgical hip dislocation technique through the femoral head fovea fenestration and impaction bone grafting for the treatment of non-traumatic osteonecrosis of the femoral head: a retrospective study - Dawei Liang; Jia Pei; Xiaohui Zhang; Ruoyan Pei; Xiantao Chen (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Background Osteonecrosis of the femoral head (ONFH) often leads to the collapse of the femoral head, ultimately resulting in patients undergoing premature total hip arthroplasty (THA). The surgical hip dislocation (SHD) technique is a type of hip-preserving surgery aimed at delaying or avoiding THA. This study aims to evaluate the clinical efficacy of SHD techniques through femoral head fovea fenestration and impaction bone grafting for the treatment of non-traumatic ONFH. Methods A retrospective analysis was conducted on the clinical data of 39 patients (39 hips) with non-traumatic ONFH who underwent SHD for treatment from 2016 to 2017. The Harris hip score (HHS) and the minimum clinically important difference (MCID) are used to evaluate clinical outcomes, while radiographic evaluations are conducted using X-rays. Kaplan-Meier survival analysis defined clinical failure as further THA, and conducted univariate survival analysis and Cox regression analysis. Any complications were recorded. Results All patients were followed up for 24–72 months, with an average of (60 ± 13.0) months. At the last follow-up, based on the HHS, 25 patients (64.1%) reported excellent and good clinical outcomes. 29 patients (74.3%) achieved MCID. Imaging evaluation of the postoperative femoral head status showed that 6 cases improved, 20 cases remained stable, and 13 cases showed progressed. Out of 39 hips, 12 hips had postoperative clinical failure, resulting in a clinical success rate of 69.2%. Association Research Circulation Osseous (ARCO) stage, China-Japan Friendship Hospital (CJFH) classification, and postoperative crutch-bearing time are risk factors for clinical failure. Postoperative crutch-bearing time of less than 3 months is an independent risk factor for clinical failure. After surgery, there was one case of sciatic nerve injury and one case of heterotopic ossification. There were no infections or non-union of the greater trochanter osteotomy. Conclusion The SHD technique through the femoral head fovea fenestration and impaction bone grafting provides a safe and effective method for treating non-traumatic ONFH, with good mid-term clinical outcomes. ARCO staging, CJFH classification, and postoperative crutch-bearing time are risk factors that affect clinical outcomes after surgery and lead to further THA. Insufficient postoperative crutch-bearing time is an independent risk factor for clinical failure.